Citric acid bioproduction: the technological innovation change. (17th February 2020) - Amato, Alessia; Becci, Alessandro; Beolchini, Francesca
Abstract: Citric acid is considered one of the most valuable weak organic acids on the market and its production by biotechnological approaches is a very interesting topic. Despite the related scientific research, the literature still lacks a state of the art for the technological innovation change, necessary for a study of the inventions designed for real scale implementation. In this context, the present review looks to account for more than 100 worldwide patents (1929–2018), necessary for the identification of the innovative markets and the most promising fields for economic investments. This deepened study identified an increasing invention number, combined with the current worldwide citric acid export flows, with China as the leader (with an economic contribution of 75%, in 2017). In order to satisfy the requests of the market which has moved toward a circular economy, the possibility to use waste substrates represents one of the main options considered in the recent patents. The discussion highlights the sustainability improvement, achieved by the conversion from a submerged technology to a solid-state fermentation ( koji process). The listed results are essential for both a scientific audience and the stakeholders involved in citric acid production, in order to have a complete and updated overview of this topic. Graphical Abstract: